Absichtliches Handeln - Horst, David (Mentis, 2012)

Actions and Accidents - Horst, David (Canadian Journal of Philosophy, 2015)

Agency and Rationality - Horst, David; Tenenbaum, Sergio (2018)

Enkratic Agency - Horst, David (European Journal of Philosophy, 2017)

Gute Gründe. Eine kritische Auseinandersetzung mit der realistischen Auffassung von Handlungsgründen - Horst, David (Lebensform und Praxisform, 2015)

Handlungen, Absichten und praktisches Wissen - Horst, David (Deutsche Zeitschrift für Philosophie, 2013)

How Reasoning Aims at Truth - Horst, David (Nous, 2021)

In Defense of Constitutivism About Epistemic Normativity - Horst, David (Pacific Philosophical Quarterly, 2022)

Is Epistemic Competence a Skill? - Horst, David (Australasian Journal of Philosophy, 2021)

Moral Worth and Skillful Action - Horst, David (Philosophy and Phenomenological Research, 2023)
Someone acts in a morally worthy way when they deserve credit for doing the morally right thing. But when and why do agents deserve credit for the success involved in doing the right thing? It is tempting to seek an answer to that question by drawing an analogy with creditworthy success in other domains of human agency, especially in sports, arts, and crafts. Accordingly, some authors have recently argued that, just like creditworthy success in, say, chess, playing the piano, or archery, creditworthy moral success is a matter of getting things right by way of manifesting a relevant skill. My main aim in this paper is to bring out an important structural difference between moral creditworthiness and creditworthiness in sports, arts, and craft, undermining attempts to use examples of the latter as a model for understanding the former. As an alternative, I propose an account of morally creditworthy action, according to which such action is a matter of manifesting virtue, not skill—a claim that's based on an important, but underappreciated, difference between the sorts of excellences constituting virtues and skills. The paper thus contributes to a more nuanced picture of normative achievements across different domains of human agency, highlighting largely overlooked structural dissimilarities among them.
CRIS-Team Scopus Importer:2023-06-23

Practical Knowledge - Horst, David (What may we believe? What ought we to do?, 2013)

Praktisches Wissen - Horst, David; Kern, Andrea (Deutsche Zeitschrift für Philosophie, 2013)

Praktisches Wissen - Horst, David; Kern, Andrea (2013)